Young People’s Attitudes toward Mobile Phones in the Republic of Macedonia - Ciunova shuleska, Anita; Grishin M.; Palamidovska sterjadovska, Nikolina (My University, 2012)
This study explores the mobile phones' attitudes and usage habits of young people in the Republic of Macedonia. The data from the survey were subjected to exploratory factor analysis, cluster analysis and ANOV A. The factor analysis identified five different factors interpreted as: fashion/status, dependency, added value, safety/security and negatives. Cluster analysis produced two segments: involved mobile phones users and indifferent mobile phone users. The ANOVA test revealed differences in the mobile phone attitudes regarding years of mobile phone use, number calls per day and the average duration of a call. The results provide useful implications for development of effective marketing strategies.
Keywords: mobile phones, attitudinal factors, customer segment